Review of the book "Orientamento e consulenza di carriera: la soddisfazione lavorativa" - Castelli, Cristina (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The book ‘Orientamento e Consulenza di Carriera: La Soddisfazione Lavorativa’ (Career Guidance and Counselling: Job Satisfaction) by Diego Boerchi, published by Edizioni Studium, represents a significant contribution in the field of career guidance and counselling. Boerchi, lecturer and researcher at the Università Cattolica del Sacro Cuore, involves 36 authors among researchers and practitioners to enrich the volume with multidisciplinary expertise. The work analyses the criticalities of the Italian labour market, highlighting the importance of a well-structured guidance system managed by trained professionals. The book delves into various theoretical approaches, such as psycho-aptitudinal, constructivist and vocational development models, applying them to improve job and training satisfaction. Intervention models, counselling tools such as tests and interviews, and innovative techniques such as autobiographical storytelling are discussed. Particular attention is given to school and university orientation, skills assessment, career coaching, and orientation for international mobility. The book also deals with inclusive orientation for prisoners, people with disabilities and political refugees. With a preface by Tiziano Treu and an afterword by Pierluigi Malavasi, the book is a valuable resource for professionals, educators and policy makers, promoting a more effective and inclusive orientation system in Italy.